2014
DOI: 10.2131/jts.39.897
|View full text |Cite
|
Sign up to set email alerts
|

Cellular effects of industrial metal nanoparticles and hydrophilic carbon black dispersion

Abstract: -The effects of five types of metal nanoparticles, gold (Au), silver (Ag), platinum (Pt), Au-polyvinylpyrrolidone (PVP) colloid, and Pt-PVP colloid, and two types of hydrophilic carbon black on cell behavior were examined. Stable nanoparticle dispersions were prepared and applied to the culture medium of human keratinocyte (HaCaT) and human lung carcinoma (A549) cells for 6 and 24 hr. Then, the mitochondrial activity (MTT assay) and the induction of cellular oxidative stress were examined. The exposure to Au a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Nanoparticles range in size from 1-100 nm and function at a molecular and cellular level. Electronic and structural properties of nanoparticles significantly differ from the respective bulk particles 2 , 3 . There are important components in the utilization of nanoparticles that include cellular uptake, adsorption, and metal ion release.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nanoparticles range in size from 1-100 nm and function at a molecular and cellular level. Electronic and structural properties of nanoparticles significantly differ from the respective bulk particles 2 , 3 . There are important components in the utilization of nanoparticles that include cellular uptake, adsorption, and metal ion release.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies indicate that the AgNP may cause antibacterial cell death due to silver ions that prevent DNA replication or inactivating cellular proteins. There are also interactions with the cell membrane in which the structure is damaged resulting in cell death 3 , 11 . Other theories suggest that silver nanoparticles cause cell death through cell lysis and thiol reactions that inactivate enzymes 3 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in recent years it has become clear that a material in the nanometric range may be more dangerous than the same material in bulk form. 14-16 If this rule is universal, it should apply also to asbestos nanofibers. 17 Additionaly, the process of malignant transformation of normal lung cells into malignant ones seems to require the direct contact of asbestos fibers with these cells, 9 and therefore it would be logical that the presence or absence of asbestos fiber in the context of the neoplastic lesion should be considered in the process of the etiological attribution of the lesion itself.…”
Section: Discussionmentioning
confidence: 99%
“…This is believed to trigger a chain reaction in which free radicals produced from the antioxidant response of PtNPs damage bacteria [19]. While one study has found that PtNPs increase the level of intracellular reactive oxygen species (ROS) [20], another study has reported that PtNPs eliminate ROS [21].…”
Section: Introductionmentioning
confidence: 99%